Cysteamine-supplemented diet for cashmere goats: A potential strategy to inhibit rumen biohydrogenation and enhance plasma antioxidant capacity - Wu, Tiecheng; Liang, Jianyong; Wang, Tao; Zhao, Ruoyang; Ma, Yuejun; Gao, Yulin; Zhao, Shengguo; Chen, Guoshun; Liu, Bin (Frontiers in Veterinary Science, 2022)
Several studies have shown that cysteamine (CS), as a feed supplement, promotes growth, though little attention has been paid to the effects of CS on the rumen microbiome. This study aimed to assess the effects of CS supplementation on microbiota diversity, metabolite production, and plasma marker interactions in cashmere goats. We randomly separated the goats into three groups (n = 10 per group) fed a basal diet supplemented with 0 (control group, CON), 60 (low CS, LCS), or 120 mg/kg/d (high CS, HCS) coated CS hydrochloride. Using 16S and internal transcribed spacer (ITS) rRNA gene amplicon sequencing, we identified 12 bacterial and 3 fungal genera with significant changes between the groups, respectively. We found a significant increase in rumen NH3-N and total volatile fatty acid (TVFA) concentrations in the LCS and HCS groups compared with the CON. With untargeted LC–MS/MS metabolomics, we screened 59 rumen differential metabolites. Among the screened metabolites, many unsaturated and saturated fatty acids increased and decreased with CS treatment, respectively. CS supplementation increased the levels of plasma total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), growth hormone (GH), and insulin-like growth factor-1(IGF-1). Rumen microbiota were highly correlated with several typical rumen metabolites, fermentation parameters, and specific plasma markers. In conclusion, CS significantly affected rumen microbiota and fermentation parameters, and ultimately inhibited the biohydrogenation of rumen metabolites, enhanced plasma antioxidant capacity, and regulated some hormones of the GH–IGF-1 axis. This study provides an overall view into the CS application as a strategy to improve health production in cashmere goats.